2009
DOI: 10.5194/bg-6-849-2009
|View full text |Cite
|
Sign up to set email alerts
|

Annual and diurnal african biomass burning temporal dynamics

Abstract: Abstract. Africa is the single largest continental source of biomass burning emissions. Here we conduct the first analysis of one full year of geostationary active fire detections and fire radiative power data recorded over Africa at 15-min temporal interval and a 3 km sub-satellite spatial resolution by the Spinning Enhanced Visible and Infrared Imager (SE-VIRI) imaging radiometer onboard the Meteosat-8 satellite. We use these data to provide new insights into the rates and totals of open biomass burning over… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
239
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(264 citation statements)
references
References 63 publications
23
239
0
2
Order By: Relevance
“…Peak anthropogenic biomass burning does not coincide with the height of the dry season, but does coincide with the middle of the burning season over the northern parts of Angola, the Democratic Republic of Congo, and Zambia, where savannah fires are often lit in July/August well before the peak of the dry season (Le Page et al, 2010). This picture is substantiated by individual fire counts based on geostationary satellite observations, which also shows peak fire activity around July/August, with peak burning of about 6 Tg per day in July (Roberts et al, 2009). In contrast, in the eastern part of South Africa and Mozambique as well as northern Namibia, the middle of the fire season is shifted toward September.…”
Section: Remote Areasmentioning
confidence: 50%
“…Peak anthropogenic biomass burning does not coincide with the height of the dry season, but does coincide with the middle of the burning season over the northern parts of Angola, the Democratic Republic of Congo, and Zambia, where savannah fires are often lit in July/August well before the peak of the dry season (Le Page et al, 2010). This picture is substantiated by individual fire counts based on geostationary satellite observations, which also shows peak fire activity around July/August, with peak burning of about 6 Tg per day in July (Roberts et al, 2009). In contrast, in the eastern part of South Africa and Mozambique as well as northern Namibia, the middle of the fire season is shifted toward September.…”
Section: Remote Areasmentioning
confidence: 50%
“…The most likely reasons include additional ageing (examination of HYSPLIT back-trajectories for these cases suggests the air masses left the African continent ∼ 5 days before arriving at Ascension Island) and the possibility that properties of the freshly emitted aerosol are different from those near Mongu. Some air masses reaching Ascension Island pass over parts of Africa north of Mongu, which are more heavily forested (Roberts et al, 2009;Adams et al, 2012), and could lead to different typical optical properties compared to savannah burning (Ward et al, 1996;Reid et al, 2005b). Unfortunately, there are no AERONET sites in this part of Africa.…”
Section: A M Sayer Et Al: Smoke Aerosol Propertiesmentioning
confidence: 99%
“…Although AERONET contains several long-term sites in the Sahel, the peak season for biomass burning there (November-February) coincides with strong dust activity, such that the aerosol is normally a mixture of biomass burning smoke and dust (Pandithurai et al, 2001;Roberts et al, 2009). Johnson et al (2008) and Eck et al (2010) found cases where these smoke aerosols were highly absorbing, with midvisible SSA as low as 0.76, although the more common cases of mixed smoke and dust in this region are less absorbing.…”
Section: Site Selectionmentioning
confidence: 99%
“…Since the initial trigger of plume rise is the heat released by the casual fire, InjH are strongly influenced by fire diurnal cycles (Roberts et al, 2009). This leads to lower nocturnal InjH which are amplified by the combination of nighttime stable atmosphere and lower PBL (Sofiev et al, 2013).…”
Section: Physics Of Landscape Fire Plumesmentioning
confidence: 99%